An mHealth Intervention Using a Smartphone App to Increase Walking Behavior in Young Adults: A Pilot Study - Walsh, Jane C; Corbett, Teresa; Hogan, Michael; Duggan, Jim; McNamara, Abra (JMIR Publications, 2016)
BackgroundPhysical inactivity is a growing concern for society and is a risk factor for cardiovascular disease, obesity, and other chronic diseases. ObjectiveThis study aimed to determine the efficacy of the Accupedo-Pro Pedometer mobile phone app intervention, with the goal of increasing daily step counts in young adults. MethodsMobile phone users (n=58) between 17-26 years of age were randomized to one of two conditions (experimental and control). Both groups downloaded an app that recorded their daily step counts. Baseline data were recorded and followed-up at 5 weeks. Both groups were given a daily walking goal of 30 minutes, but the experimental group participants were told the equivalent goal in steps taken, via feedback from the app. The primary outcome was daily step count between baseline and follow-up. ResultsA significant time x group interaction effect was observed for daily step counts (P=.04). Both the experimental (P<.001) and control group (P=.03) demonstrated a significant increase in daily step counts, with the experimental group walking an additional 2000 steps per day. ConclusionsThe results of this study demonstrate that a mobile phone app can significantly increase physical activity in a young adult sample by setting specific goals, using self-monitoring, and feedback.